Champions, respect and emotions in Physical Education in Argentina between 1946 and 1955 - Pablo Orbuch, Iván (2020)
In Argentina, between 1946 and 1955, the impulse to body education was increasing. From the perspective of the Peronist government, Physical Education was a firm ally to achieve self-control and the regulation of emotions in young people who attended school. A group of advanced students of the aforementioned functional subject as a transmission belt of the official postulates, insofar as they were possessors of specific attributes that allowed them to enjoy the trust of their peers. Respect can be cited among them. It was the champions who had a special regulation that governed all their actions. It ranged from clothing to personal qualities that they should have. In the case of this research, it will address what happened in schools where only women attended. The speeches of the directors of educational institutions allow us to understand the different space that emotions had in Physical Education classes in Argentina governed by Juan Domingo Perón.